(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
In the present study a rapid, accurate and precise chiral HPLC method was developed and validated for enantiomeric separation of racemate citalopram and escitalopram according to the guidelines of United States of Pharmacopeia (USP) and International Conference on Harmonization (ICH). The chiral chromatographic separation was achieved with ammonium acetate/ ethanol/ 2-propanol/ methylene dichloride (100 : 150 : 70 : 30, v/v) at a flow rate of 0.5 ml/min using a chiral CD-PH column. The HPLC analyses were monitored at 254 nm. The method showed a good linearity with regression coefficient (r2) of 0.998 in the range of 20.0-70.0 μg/ml for escitalopram. The detection limit (LOD), quantitation limit (LOQ) and average percentage of recovery for escitalopram were found to be 2.54, 7.68 μg/ml and 100.28% to 102.86%, respectively. The percentage of relative standard deviation (%RSD) for intra- and inter- day precision were found as 0.16% and 0.09%, respectively. The established method proved as reproducible with a %RSD value of less than 2 and having the robustness within specified limit. The present study also showed the enantiomeric purity or excess (%ee) of seven pharmaceutical preparations of escitalopram. Thus the proposed chiral method can be applied for the enantiomeric purity determination of escitalopram formulations. Dhaka Univ. J. Pharm. Sci. 16(2): 165-172, 2017 (December)